DOP42 Dietary therapies induce rapid response and remission in active paediatric Crohn's disease. (25th January 2019) - Sigall Boneh, R; Van Limbergen, J; Assa, A; Shaoul, R; Wine, E; Milman, P; Cohen, S; Kori, M; Peleg, S; On, A; Shamaly, H; Abramas, L; et al.
Abstract: Background: Dietary therapies are increasingly utilised to induce remission in children with active Crohn's disease (CD). Medical therapies such as steroids and anti-TNF induce rapid response within the first 2–3 weeks. The goal of this study was to evaluate the early response rate (significant response or remission) in response to two different dietary therapies by Week 3 and to assess whether response by Week 3 was predictive of remission by Week 6. Methods: We utilised the data from the 3 and 6 week visits in the Crohn's disease exclusion diet (CDED) trial, which was a multi-centre randomised controlled trial using two different and successful strategies for induction of remission. It was conducted among children with mild-to-moderate luminal CD, receiving either exclusive enteral nutrition (EEN), using 100% of calories from EN (Modulen, Nestle Health) or the CDED with partial enteral nutrition (PEN; 50% of calories from PEN). Patients were evaluated at baseline, Week 3, and Week 6. Remission was assessed by the use of the paediatric Crohn's disease activity index (PCDAI; defined as a PCDAI ≤10) using intention to treat (ITT) analysis. Response was defined as a drop in ITT PCDAI of 12.5 points or remission. Response, remission, CRP, albumin, and adherence to diet were evaluated at each visit. Results: Seventy-four patients were randomised, 40 allocated to CDED+PEN and 34 to EEN. Mean (±standard deviation) age was 14.2 ± 2.7 years in total cohort. Pooled response rate was present in 61/74 (82.4%) patients by Week 3. Pooled remission rate was obtained in 69% by Week 3. By Week 6, 56/74 patients were in ITT clinical remission (75.6%). Among patients in remission at Week 6, 85% were already in clinical remission by Week 3, and a significant drop in inflammation was present (Table 1) Table 1. Clinical and inflammatory parameters. Among patients in remission at Week 6, 54/56 (96.4%) had obtained a good response or remission to therapy by 3 weeks. Conclusions: Dietary therapy caused a rapid clinical improvement and response by Week 3, which was equivalent with both diets. Patients who failed to respond by Week 3 were unlikely to reach remission by Week 6.